Herbs and Spices New Processing Technologies - Shabir Ahmad, Rabia (IntechOpen, 2021)
Herbs and Spices - New Processing Technologies is a collection of research and review chapters offering a comprehensive overview of recent developments in the field of herbs and spices, with a focus on plants containing bioactive components and the utilization of novel processing technologies in the development of functional products. The book consists of four sections containing fourteen chapters written by various researchers and edited by an expert active in the research of plants and bioactive compounds.